Correction: Tailored high performance shape memory epoxy–silica nanocomposites. Structure design. Issue 18 (20th April 2016) - Ponyrko, S.; Donato, R. K.; Matějka, L.
Abstract : Correction for 'Tailored high performance shape memory epoxy–silica nanocomposites. Structure design' by S. Ponyrko, et al., Polym. Chem., 2016, 7, 560–572.